Oral lacerations during motocross: A case report. Issue 6 (31st August 2017) - Hino, Shunsuke; Takeda, Akio; Kaneko, Takahiro; Horie, Norio; Shimoyama, Tetsuo
Abstract: Motocross is a high‐risk sport that can cause serious injuries including oral injuries. However, mouthguard use is not mandatory in motocross. This report describes a case of an oral laceration with exposure of bilateral inferior alveolar nerves as a result of a motocross accident in which the patient was not wearing a mouthguard.